Annual report of the Australian National Enterovirus Reference Laboratory, 2012 - Roberts, Jason; Hobday, Linda; Ibrahim, Aishah; Aitken, Thomas; Thorley, Bruce (Communicable Diseases Intelligence, 2013)
In 2012 no cases of poliomyelitis were reported through clinical surveillance in Australia, and poliovirus was not detected through virological surveillance. Australia conducts surveillance for cases of acute flaccid paralysis (AFP) in children less than 15 years as the main mechanism to monitor its polio-free status in accordance with World Health Organization (WHO) recommendations. Cases of AFP in children are notified to the Australian Paediatric Surveillance Unit or the Paediatric Active Enhanced Disease Surveillance System. In 2012 Australia reported 1.2 non-polio AFP cases per 100,000 children, meeting the WHO performance criterion for a sensitive system for the fifth year in a row. However the faecal specimen collection rate from AFP cases was 29%, which was well below the WHO target of 80%. Virological surveillance for poliovirus consists of two components. Firstly, the Enterovirus Reference Laboratory Network of Australia (ERLNA) reports on the typing of enteroviruses detected in or isolated from clinical specimens. Secondly, environmental surveillance is conducted at sentinel sites. These surveillance systems are co-ordinated by the National Enterovirus Reference Laboratory (NERL).